THE BACKGROUND DNA DAMAGE LEVEL IN PERIPHERAL BLOOD CELLS IN HALABJAS' SURVIVORS-KRG-IRAQ - OTHMAN, GALAWEZH OBAID; NAJEEB, HISHYAR AZO; AHMED, GHAZWAN FAWZI; SULAIMAN, KHAZAL MUHAMMAD (Journal of Duhok University, 2023)
The inhabitants of communities in the Kurdistan area of Iraq, particularly Halabja, represent the greatest civilian populations ever exposed to chemical weapons. In several sections of the Kurdistan Region of Iraq between 1987 and 1991, the Iraqi government conducted a Genocide against Kurds. Various chemical warfare chemicals, such as sulfur mustard and the nerve agents Sarin, Tabun, and cyanide, were used in the act of war. There are scientific indications that chemical weapons alter DNA and causes genetic lesions and mutation which may eventually cause health problems. Survivors in this city are till now suffering from a variety of health complaints from mild to severe and fatal one as a result of the long-lasting effects of chemicals used in bombing the city. From the several health complains developed among survivors of Halabja bombardment were cancer, respiratory, ophthalmological, dermatological, reproductive and immunological complains. It was required for measuring the background DNA damage level in peripheral cells in some survivors of Halabja city. The Alkaline Comet Assay data reveals varying degrees of DNA damage level in Halabja survivors and in those born after the chemical attack in the same city. The damage level was significantly greater in Halabja survivors in comparison to those individual living in Duhok city (age/sex matched). However, the DNA damage measured in younger generation (those were born after the chemical attack in Halabja) is minimum, this could refer that only the exposed survivors at risk of genomic instability